Transition Temperature in Thermochromic Liquid Crystals using Second-Order Features Extraction - Cindyawati Cindyawati; Risti Suryantari (Department of Physics, Sebelas Maret University, 2023)
Liquid crystals are a type of substance that has solid and liquid properties. One of the types of it is cholesteric. Cholesteric liquid crystals have a characteristic which is called pitch. Pitch is very sensitive to changes in temperature. The pitch will reflect different colors depending on the wavelength at a particular temperature. Thermochromic Liquid Crystals (TLC) is the cholesteric liquid crystals material sold commercially. At the transitional temperature, the texture of TLC changes, so the reflected color will also change. Second-order feature extraction was chosen to determine the change in texture with the transition temperature. The TLC layer was made by thickness of 100 µm. This layer was heated and observed using a polarizing microscope with an angle between the polarizer and analyzer of 90o. The obtained result are cross patterns emerged at anisotropic transition temperature and higher temperature on TLC will lead to an isotropic phase.